Adiponectin Signaling Regulates Lipid Production in Human Sebocytes - Jung, Yu Ra; Lee, Jin-Hyup; Sohn, Kyung-Cheol; Lee, Young; Seo, Young-Joon; Kim, Chang-Deok; Lee, Jeung-Hoon; Hong, Seung-Phil; Seo, Seong-Jun; Kim, Seong-Jin; Im, Myung (PLOS ONE, 2017)
Adiponectin plays important roles in metabolic function, inflammation and multiple biological activities in various tissues. However, evidence for adiponectin signaling in sebaceous glands is lacking, and its role remains to be clarified. This study investigated the role of adiponectin in lipid production in sebaceous glands in an experimental study of human sebocytes. We demonstrated that human sebaceous glands in vivo and sebocytes in vitro express adiponectin receptor and that adiponectin increased cell proliferation. Moreover, based on a lipogenesis study using Oil Red O, Nile red staining and thin layer chromatography, adiponectin strongly upregulated lipid production in sebocytes. In three-dimensional culture of sebocytes, lipid synthesis was markedly enhanced in sebocytes treated with adiponectin. This study suggested that adiponectin plays a significant role in human sebaceous gland biology. Adiponectin signaling is a promising target in the clinical management of barrier disorders in which sebum production is decreased, such as in atopic dermatitis and aged skin.